Structure-Dependent Nickel-Catalysed Transposition of N-Allylamides to E- or Z-Enamides - Weber, Felicia; Steinlandt, Philipp S.; Ballmann, Monika; Hilt, Gerhard (Synthesis, 2017)
The nickel-catalysed transposition of a carbon–carbon double bond of N-allyl and N-homoallyl amides is described. While the transposition of acyclic amides gave very high Z-selectivity of the enamides, corresponding cyclic N-allyl amides led exclusively to the E-configured products. Thereby, we realised a stereodivergent approach to enamides that is dependent on the structure of the amide substituents. When homoallylic substrates are used, a temperature-controlled single transposition to a Z-allylic amide derivative at low temperature or a double transposition to an E-enamide at elevated temperature could be achieved.
Keywords: allyl amides; double bond translocation; enamides; nickel; stereoselectivity